A Decision‐Support Approach for Provider Scheduling in a Patient‐Centered Medical Home. Issue 1 (January 2017) - Konrad, Renata; Ficarra, Sarah; Danko, Catherine; Wallace, Rachel; Archambeault, Cliona
Abstract : EXECUTIVE SUMMARY : The patient‐centered medical home (PCMH) has been proposed as a viable and medically effective model of primary care delivery. The fundamental principles of a PCMH address increased access and offer new ways to organize a practice. Creating provider schedules able to satisfy the operational and organizational constraints imposed by this type of delivery model is a challenging, complex, and time‐consuming task. This article presents a two‐step approach for scheduling providers and prospectively assessing the consequences of various schedules on patient throughput without experimenting on the real‐world system. The first step uses an original integer programming model to address the tactical planning problem of assigning provider duties to defined shifts while incorporating a number of constraints. Given provider scheduling preferences and availability, a monthly schedule is determined to satisfy the expected demand. The second step consists of quantifying capacity increases that result from adjustments to operating hours, physician availability, and examination room availability. A discrete‐event simulation model is used to assess the impact of various proposed operating configurations on patient throughput.